The beginning of prophethood and the stages of Islamic call during the Meccan period in (Kitab Al-Umm) by Al-Shafi’i - Suliman, Haliz; Ahmed, Khatab (Humanities Journal of University of Zakho, 2024)
The history of the prophet's life (peace be upon him) begins with the revelation. Furthermore, historians give importance to the pre-Islamic period, meaning the conditions of people before the Islamic religion. Additionally, Muhammad's choice (peace be upon him) for prophecy. This invitation is divided into two phases in Mecca: the secret invitation phase lasted for three years in the first year of the prophecy, 610 AD. And the stage of declaration of the invitation is also divided into two stages: the stage of the prophet's invitation (peace be upon him) to his close relatives, and the stage of invitation to people in general and the people of Mecca in particular. This stage ended with the migration of Muslims to Medina in the thirteenth year of the prophecy. Imam Al-Shafi'i, may God have mercy on him, in his book Al-Umm, which is the primary focus of this research, conveys to us all this information in the various parts of his book, utilizing verses of the noble Quran and the Hadiths of the Prophet as evidence for his opinions on every topic he posed.